2016
DOI: 10.1016/j.bcp.2016.08.010
|View full text |Cite
|
Sign up to set email alerts
|

KR-33028, a potent inhibitor of the Na+/H+ exchanger NHE1, suppresses metastatic potential of triple-negative breast cancer cells

Abstract: Hyper-activation of the Na + /H + exchanger NHE1 occurs at the onset of oncogenic transformation and plays a critical role in breast cancer carcinogenesis. Dysregulation of NHE1 activity results in intracellular alkalinization and the acidification of the extracellular tumor microenvironment that promotes metastasis. Hence, the use of chemical inhibitors of NHE1 as chemotherapeutic agents is an alluring prospect. We previously demonstrated that two structurally different NHE1 functions that are predictive of m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 28 publications
(54 reference statements)
1
17
0
Order By: Relevance
“…Importantly, constitutive increases in pH i have been linked to increased migration in cancer cell models (Amith et al, 2015(Amith et al, , 2016aParks and Pouyssegur, 2015;Lin et al, 2012;Cong et al, 2014), and we have recently shown that increased pH i enables cancer cell invasion in an animal model (Grillo-Hill et al, 2015). Importantly, in these studies, decreasing pH i inhibits the migration or invasion phenotype, suggesting that lowering the pH i of cancer cells as part of cancer therapy can limit metastasis.…”
Section: Migration and Metastasismentioning
confidence: 78%
See 1 more Smart Citation
“…Importantly, constitutive increases in pH i have been linked to increased migration in cancer cell models (Amith et al, 2015(Amith et al, , 2016aParks and Pouyssegur, 2015;Lin et al, 2012;Cong et al, 2014), and we have recently shown that increased pH i enables cancer cell invasion in an animal model (Grillo-Hill et al, 2015). Importantly, in these studies, decreasing pH i inhibits the migration or invasion phenotype, suggesting that lowering the pH i of cancer cells as part of cancer therapy can limit metastasis.…”
Section: Migration and Metastasismentioning
confidence: 78%
“…Supporting this idea, lowering pH i through genetic knockdown or inhibition of ion transporters reduces cell proliferation and migration Amith et al, 2016a;Le Floch et al, 2011), cell invasion (Yang et al, 2010), and suppresses tumorigenesis in xenograft models (Amith et al, 2015;Lagarde et al, 1988;Sonveaux et al, 2008;Colen et al, 2011;Chiche et al, 2012). Additionally, we have recently shown in Drosophila animal models and human clonal cells that, by lowering the pH i , we can induce synthetic lethality with expression of activated oncogenes -notably Raf and Raspossibly by limiting the efflux of metabolically generated acids (Grillo-Hill et al, 2015).…”
Section: Tumorigenesismentioning
confidence: 94%
“…The Na + /H + -exchanger 1 (NHE1) binds Ca 2+ /CaM at its C-terminal region preventing auto-inhibition, and upregulation of this transport system plays an important role in EMT and metastasis development in triple-negative human breast carcinoma, a process that is inhibited by a specific NHE1 inhibitor [302,303]. CaM plays an important role in this process, as cells expressing a NHE1 with a mutation of the CaM-binding site that yields a constitutive active protein, showed enhanced migration, invasion, and spheroid growth, suggesting an increase of the metastatic potential of these carcinomas [302].…”
Section: Other Cam-binding Proteinsmentioning
confidence: 99%
“…We have recently tested a new, more selective and potent NHE1 inhibitor, KR-33028, (88) in MDA-MB-231, MDA-MB-468, and Hs578T cells, which are representative of multiple TNBC subtypes. It was very effective in reducing rates of migration, invasion and clonogenic colony growth, all of which are characteristics that are predictive of metastasis in patients, A related approach to decrease NHE1 activity is to affect NHE1 regulation.…”
Section: Nhe1 Inhibition As a Chemotherapy Strategy: The Challenge Ofmentioning
confidence: 99%